The actions of prostaglandins E(1) and F(2a) on the perfused vessels of the isolated rabbit ear - Al Tai, Suhaila A. (1972)
1. In the isolated rabbit ear vascular bed, perfused with Krebs solution, prostaglandins E(1) and F(2α) produce dose-dependent, phentolamine-sensitive constrictions. 2. These are absent if the animal is pre-treated with reserpine or if the ear is denervated in advance. 3. If noradrenaline or vasopressin is added to the Krebs solution, vascular resistance is high and PGE(1) and PGF(2α) produce vasodilatation which is unaffected by hyoscine or propranolol. 4. Perfusion with theophylline, with added ATP, ADP or 3′5′-AMP, or pre-treatment of the animal with stilboestrol antagonizes the dilator response to PGE(1) in the presence of noradrenaline, which may be reversed. Most of the responses to PGF(2α) are reversed. These treatments elevate the level of 3′5′-AMP in tissues. 5. It is postulated that prostaglandins exert a regulatory action on 3′5′-AMP levels through inhibition of adenyl cyclase and/or phosphodiesterase and that the resulting rising or falling level of 3′5′-AMP determines the nature of the response by the smooth muscle to the released noradrenaline.